Are antidepressants useful in bipolar disease? - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2017)
The treatment of bipolar depression is the subject of intensive research, as shown by the numerous references obtained only in the last year using the terms "bipolar depression and treatment" in MEDLINE. This is one of the signs of effervescence in the treatment of this affection leading to publication of consensus in North America and the United Kingdom which often don't deal with clinical realities [1].